2018
DOI: 10.3389/fpubh.2018.00358
|View full text |Cite
|
Sign up to set email alerts
|

Elder Abuse—The Current State of Research in South Africa

Abstract: Objectives: The concern about elder abuse increases as the global population ages. Elder abuse is a global public health, human rights, and criminal justice problem that goes beyond socioeconomic classes and regions. It remains understudied, especially in developing countries with limited resources. It is therefore timely to do a review of the available research on elder abuse in South Africa, to be able to address the gaps in the research with future projects.Methods: Publications were identified from PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Elderly abuse was found to be prevalent among participants who were female, illiterate, belonged to the Dalit caste group, low financial situation, tobacco users, and poor health. These results agree with those of several other studies [ 25 , 31 , 32 , 36 , 37 ]. Other research have shown that elderly people who were ill are more likely to be abused [ 19 , 38 ].…”
Section: Discussionsupporting
confidence: 94%
“…Elderly abuse was found to be prevalent among participants who were female, illiterate, belonged to the Dalit caste group, low financial situation, tobacco users, and poor health. These results agree with those of several other studies [ 25 , 31 , 32 , 36 , 37 ]. Other research have shown that elderly people who were ill are more likely to be abused [ 19 , 38 ].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, social workers could be motivated by the perception that elder abuse is a developmental deficit-related issue with psychosocial effects. However, research from South Africa identifies elder abuse as a structural and cultural issue that requires structurally and culturally relevant interventions (Kotzé, 2018). Therefore, this study highlights that social workers should design structurally and culturally appropriate interventions to tackle elder abuse.…”
Section: Discussionmentioning
confidence: 95%
“…Participants were concerned with revamping the role of the family and social network systems that they believed had been weakened by modernisation. The need for cultural and structural solutions to ageing challenges is well-articulated in the writings of Kotzé (2018) and Wamara (2021), who identify elder abuse as a structural and cultural issue that necessitates culturally appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in different countries report similar high and worrying figures. For instance, 64% of the institutional staff working with older people in South Africa admitted to elder abuse (Kotzé, 2018), and in Kenya, 81.1% of older people had experienced some form of abuse (Lydiah Kabole et al, 2013).…”
Section: Introductionmentioning
confidence: 99%